Análise dialélica das capacidades geral e específica de combinação utilizando técnicas uni e multivariadas de divergência genética em mamoneira (Ricinus communis L.) - Costa, Mauro Nóbrega da (2006)
Techniques of dialell crossings and genetic divergence with application of canonical variables and principal components have been applied with the objective of evaluating six castor bean genotypes behaviorconsidering the variables days to flowering (FR), number of racemes per plant (NRP), effective length of the primary raceme (CR), plant height (AP), potential yield (PP) and oil content (TO), when choosing promising parents in breeding programs through hybridizations. Griffing’s scheme of diallel crossings (1956) was used when evaluating combining capacities. A randomized complete blocks design with four replications was used and the trial was set at irrigation condition, at Embrapa-Algodão Experimental Station – CNP, placed in the municipal district of Barbalha-CE. Variable AP presented significance only for the effect of the general capacity of combination (CGC), while PP showed significance only for specific capacity of combination (CEC). Both CGC and CEC effects were significant for the other variables. However, the quadratic components indicated predominance of non-additive genic effects for all of the variables. Parent BRA 4871 (1), BRS Paraguaçu (2) and BRS Nordestina (5) had been distinguished as good general combiners for FR; BRS Nordestina (5), for NRP; BRA 2968 (4), BRA 5550 (6) and BRS Nordestina (5) for CR. For the variable plant height, the best general combinadores were: BRA 4871 (1), BRS Paraguaçu (2) and BRA 7722 Papo-de-gia (3). BRS Nordestina (5) and BRA 5550 (6) were pointed as good combinadores for PP, while BRS Nordestina was configured as a good combiner for TO. Those genotypes involvement in improvement programs in order to obtain new varieties starting from advanced selection generations can be promising. In a multivariate context, two principal components and two canonical variables were enough to explain 78% and 82% of the total variance, respectively. The first principal component (CP1) presented positive relationship with the variables NRP, AP and PP, while the second component (CP2) presented positive relationship with FR and CR. The first canonical variable (VC 1) turned out to be positively related to FR and CR and, on the other hand, negatively related to NRP and PP. Instead, for the second canonical variable (VC2), a contrast was verified among positive values for CR, PP and TO and negative values for AP. There was an indication of genetic divergence among parents with larger discrimination observed by the principal compounds technique. Nevertheless, low correlations had been detected between genetic distance of parents and heterosis for both techniques. Parent BRA 5550 (6) presented the largest positive estimate of CGC for CP1 and the best hybrid combinations for CEC were BRA 4871 x BRA 5550 (1x4) and BRA 2968 x BRS Nordestina (4x5). Like CP2, BRS Nordestina (5) was pointed as a good general combiner, while the best combinations when it comes to CEC were BRA 4871 x BRA 2968 (1x4) BRS Paraguaçu x BRA 2968 (2x4), BRA 7722 Papo-de-gia x BRA 2968 (3x4) and BRA 7722 Papo-de-gia x BRS Nordestina (3x5), with favorable contribution to (CR), while BRA 4871 x BRA 7722 Papo-de-gia (1x3), BRS Paraguaçu x BRA 7722 Papo-de-gia (2x3) and BRS Paraguaçu x BRS Nordestina (2x5) were pointed as favorable to FR. Parents BRS Paraguaçu (2), BRS Nordestina (5) and BRA 4871 (1) presented good general capacity of combination for VC1, while BRS Nordestina (5) was the only favorable parent for VC2, because they contribute with genes to a larger effective length of the primary raceme, yield potential and oil content, plus genes for plant high reduction. BRA 4871 x BRA 7722 Papo-de-gia (1x3), BRA 4871 x BRA 5550 (1x6), BRS Paraguaçu x BRA 7722 Papo-de-gia (2x3), BRS Paraguaçu x BRS Nordestina (2x5) and BRA 2968 x BRS Nordestina (4x5) presented a better behavior about CEC for VC1. BRS Paraguaçu x BRA 2968 (2x4) and BRA 2968 x BRS Nordestina (4x5) were the best combinations for VC2. Hybrid BRA 2968 x BRS Nordestina (4x5) represents the best exploration perspective in breeding because of its favorable medium performance for all of the features and a better heterosis behavior about VC2. Hybrid combinations BRA 4871 x BRA 7722 Papo-de-gia (1x3), BRA 4871 x BRA 5550 (1x6), BRS Paraguaçu x BRA 7722 Papo-de-gia (2x3), BRS Paraguaçu x BRA 2968 (2x4), BRS Paraguaçu x BRS Nordestina (2x5) and BRA 2968 x BRS Nordestina (4x5) could be used in order to create a new basis-population, starting from intercrossings among them, both for exploration through intrapopulation selection appealing and for the extraction of lineages destined to the synthesis of hybrids able to gather precocity, larger number of racemes per plant, lower plants height, higher yield potential and larger oil content.